Inclusion Is the key ingredient to innovative leadership : when leaders value and model inclusion, they can increase psychological safety and enhance performances on their teams - Tulshyan, Ruchika; Clearfield, Chris (MIT Sloan Management Review, 2022)
Ruchika Tulshyan believes that the No. 1 trait among innovative leaders is simple: inclusion. The author, speaker, and founder of diversity and inclusion strategy firm Candour has dedicated her career to teaching leaders how to implement diversity and inclusion practices that actually have an impact. In this Q&A, Tulshyan discusses the importance of self-awareness, psychological safety, and the ability to recognize and learn from past mistakes.